Fatwa DSN MUI Nomor 86/DSN-MUI/XII/2012 Tentang Hadiah Dalam Penghimpunan Dana Lembaga Keuangan Syariah: Implementasi Pada BMT UGT Sidogiri Pasuruan - Khoirun Nisak; Irham Zaki (Jurnal Ekonomi Syariah Teori dan Terapan, 2017)
This research aimed to analyze the implementation process of the indonesian council of ulama (DSN MUI) regulation number 86/DSN-MUI/XII/2012 on the prize fund of Islamic financial insitutions in the Baitul Maal Wat Tamwil (BMT) UGT Sidogiri Pasuruan. The method used in this research is qualitative approach using case study strategy in BMT UGT Sidogiri Pasuruan. The data collection was done by interview and documentation. The validation technique used is triangulation technique of sources. The analysis techniques in this research uses Miles and Huberman Theory.The results of this research based on the indonesian council of ulama (DSN MUI) regulation number 86/DSN-MUI/XII/2012 on the prize fund of Islamic financial insitutions. Based on the analysis done by researches, BMT UGT Sidogiri Pasuruan has not been effective yet in applying regulation issued by DSN MUI, especially on the regulation number 86/DSNMUI/XII/2012, at the ban point of making prize program as a habit